Midline survey: Transforming teacher education and learning - T-TEL (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:MJM6PHCK 2405685:UMGJ8LUJ

Annual Survey of Progress and Achievement - T-TEL (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8MWHYQCT 2405685:PSLM9PT6

Transforming Teaching, Education & Learning Directors' Report 2022 - 2023 - T-TEL (Transforming Teacher Education and Learning, 2023)
T-TEL's 3rd Annual General Meeting (AGM) Report
KerkoCite.ItemAlsoKnownAs: 2339240:QIY6C2M5 2405685:9HQR35CW

OER Guidance for Colleges - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2405685:VCK4YCEW

Theme 5: Teaching and Learning Materials (Professional Development Guide For Student Teachers) - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2405685:Q6V7CX64

T-TEL's Terms, Messages and Communications Guide - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:7GKEEIDQ

Open Educational Resources: Guidance for College of Education - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2405685:4G26UDAG